THE USE OF METAPHOR IN BARACK OBAMA’S INAUGURATION SPEECH - Risdianto, Faizal (Universitas Negeri Semarang, 2014)
This study aims to elaborate the uniqueness of Barack Obama’s inaugural speech after he was sworn in as the 44th US president at 20 January 2009. This research is a (qualitative) bibliographical study. The object of the study is the the use of metaphor in Barrack Obama’s speech. There were 23 sentences chosen to represent all the metaphorical sentences of Obama’s speech being the object of the study. Having analyzed the data by the perspective of Lakoff and Johnson’s conceptual metaphor, the researcher drew a conclusion that Obama effectively and creatively used metaphorical expressions in convincing his people about his future plans. His remarkable speech discussing how to solve the great scale of the economic mess that now confronts the US and the common feeling of the loss of national self-confidence.